A feasibility and load sensitivity analysis of photovoltaic water pumping system with battery and diesel generator. (15th September 2017) - Muhsen, Dhiaa Halboot; Khatib, Tamer; Haider, Haider Tarish
Highlights: Feasibility and load sensitivity analysis is conducted for PVPS. Battery and diesel generator are considered as supporting units to the system. The configuration of the PV array and the initial status of the tank are important. The COU is more sensitive to the capital cost of PV array than other components. Increasing the maximum capacity of water storage tank is better storage and DG. Abstract: In this paper, a feasibility and load sensitivity analysis is conducted for photovoltaic water pumping systems with storage device (battery) or diesel generator so as to obtain an optimal configuration that achieves a reliable system. The analysis is conducted based on techno-economic aspects, where the loss of load probability and life cycle cost are represented as technical and economic criteria, respectively. Various photovoltaic water pumping systems scenarios with initially full storage tank; battery and hybrid DG-PV energy source are proposed to analyze the feasibility of system. The result shows that the configuration of the PV array and the initial status of the storage tank are important variables to be considered. Moreover, the sensitivity of cost of unit for various PVPS components is studied. It is found that the cost of unit is more sensitive to the initial capital cost of photovoltaic array than other components. In this paper a standalone PV based pumping system with a PV array capacity of 2.4 kWp and a storage tank with a capacity of 80 m 3 was proposed an a optimum system. The system with the aforementioned configuration pumps an average hourly water volume of approximately 3.297 m 3 over one year with a unit of 0.05158 USD/m 3 . Moreover, according to results, increasing the maximum capacity of water storage tank is technically and economically better than supporting a photovoltaic water pumping systems with another energy source or extra storage device.